Inscribing place in Singapore: Instagram depictions of hauntedness. Issue 3 (27th May 2022) - Kaur, Ershen; Graham, Connor; Kai, Koh Hong
Abstract: In this article we examine the construction and circulation of images of a purportedly haunted house in Singapore's folklore, Istana Woodneuk, through Instagram. Analyzing a corpus of 960 Instagram images, we first identify 14 tropes and then two overarching themes – haunted-place making and subversive imaging. We make three main points in this article. Firstly, we argue that the creation of Istana Woodneuk Instagram posts can be understood only against the backdrop of national anxieties about the constraint and control of land and history. Secondly, and relatedly, we posit that the bottom-up creation and collective sharing of these posts is an assertion of young Singaporean identity against a larger state narrative. Istana Woodneuk, in its ambiguity and hauntedness, along with Instagram's affordances, gives young Singaporeans a unique unregulated space for escape from "reality" and control. Thirdly, we argue that these Instagram posts blend frivolity and thoughtlessness with resistance and self-expression, where personal stories weave into a larger communal narrative that offers bottom-up alternatives to the state sponsored "Singapore Story." This intersection between Istana Woodneuk as a space, in contrast to other state-defined delineated places of death, and the infrastructural properties of Instagram are crucial to the construction of this larger narrative.